Assessment of medical intern’s knowledge, awareness and practice of familial hypercholesterolemia at academic institutes in Jeddah, Saudi Arabia - Alzahrani, Sami H. (Lipids Health Dis, 2020)
BACKGROUND: Familial Hypercholesterolemia (FH) is a serious under-diagnosed disease characterized by raised low-density lipoprotein cholesterol (LDL-C) and premature coronary artery diseases (CAD). The scarcity of FH reported patients in Saudi Arabia indicates lack of FH awareness among physicians. OBJECTIVE: The goal of this research was to assess knowledge, awareness, and practice (KAP) about FH disorder among Saudi medical interns and to identify areas that need educational attention. METHODS: This cross-sectional study involved 170 Saudi medical interns (83 males and 87 females) from academic institutes in Jeddah, Saudi Arabia. The interns were asked to fill an online FH-KAP questionnaire. Total score for each separate domain measured by adding correct answers. RESULTS: Although, knowledge of FH definition (76.5%) and classical lipid profile (52.4%) were reasonable; knowledge on inheritance (43.5%), prevalence (12.4%) and CAD risks (7.1%) were poor. Knowledge score was significantly higher in female than male (7.5 ± 3 vs. 5.3 ± 2.6, P < 0.001). Regarding awareness, 54.1% were familiar with FH disorder, 50.6% with the presence of lipid clinic but only 16.5% were acquainted with guidelines. Furthermore, in the practice domain 82.9% selected statin as first line treatment and 62.9% chose routinely checking the rest of the family, while 15.3% chose ages 13–18 years to screen for hypercholesterolemia in patients with a positive family history of premature CAD. CONCLUSION: Substantial defects in FH-KAP among Saudi medical interns were found, emphasizing the importance of professional training. Extensive and constant medical education programs as early as an internship are required to close the gap in CAD prevention.